2018
DOI: 10.3390/min8070295
|View full text |Cite
|
Sign up to set email alerts
|

Reprocessing of a Southern Chilean Zn Tailing by Flotation—A Case Study

Abstract: The reprocessing of tailings can have economic and environmental benefits compared to the processing of primary ore deposits. In this paper we present the characterization of a tailings dam in southern Chile by means of mineralogical and geochemical investigations, focusing on sphalerite and trace elements with the aim to investigate a potential reprocessing. The assessment is followed by a flotation study, focusing on the recovery of sphalerite with a high selectivity towards sulfidic and non-sulfidic gangue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…There have been numerous recent studies investigating the potential for reprocessing tailings ores using froth flotation for a variety of different ore types such as copper (Lutandula and Maloba, 2013;Alcalde et al, 2018;Mackay et al, 2018;Yin et al, 2018), gold (Valderrama and Rubio, 2007), zinc (Yang et al, 2015;Babel et al, 2018) and cassiterite (Leistner et al, 2016). These studies have shown that there is good potential for the reprocessing of the various tailings types investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous recent studies investigating the potential for reprocessing tailings ores using froth flotation for a variety of different ore types such as copper (Lutandula and Maloba, 2013;Alcalde et al, 2018;Mackay et al, 2018;Yin et al, 2018), gold (Valderrama and Rubio, 2007), zinc (Yang et al, 2015;Babel et al, 2018) and cassiterite (Leistner et al, 2016). These studies have shown that there is good potential for the reprocessing of the various tailings types investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The small grains facilitated the chemical treatment and metal extraction [20,32] in coarser fractions from the crown of construction, which enable mechanical separation in first step of enrichment. Chalcopyrite grains are the most frequently occurring component in separate grains in both ZM and OS tailings (Figures 4 and 5), useful for copper extraction [32,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Characterising tailings storage facilities will also introduce other operational stakeholders into the project, such as geophysicists and geochemists. As tailings are a near-future resource for many mining operations (e.g., Savage River mine, Tasmania; Rosebery mine, Tasmania; Century mine, Queensland), the area should be investigated, funded, and researched now with operators encouraged to explore for commodities other than that being mined (e.g., critical metals in base metal deposits) [94,98]. Mineral processing technologies and deficiencies have changed so much since many of the tailings facilities were constructed that there is significant potential for reserves, with biohydrometallurgical methods particularly well suited to extracted refractory metals [99].…”
Section: Waste Management and Recyclingmentioning
confidence: 99%